Evaluation of the performance of a pairs trading strategy of JSE listed firms - Naicker, Shreelin (My University, 2016)
A pairs trading strategy is a market neutral trading strategy that tries to make a profit by making use of inefficiencies in financial markets. In the equity pairs trading context, a market neutral strategy, is a strategy that hedges against both market and sector risk. According to the efficient market theory in its weak form, a pairs trading strategy should not produce positive returns since the actual stock price is reflected in its past trading data. The main objective of this paper is to examine the performance and risk of an equity pairs trading strategy in an emerging market context using daily, weekly and monthly prices on the Johannesburg Securities Exchange over the period 1994 to 2014. A bootstrap method is used determine whether returns from the strategy can be attributed to skill rather than luck.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Finance and investment. Johannesburg, 2015
Keywords: Johannesburg Stock Exchange; Stocks--Prices--South Africa